Capital Operating Time and total Factor Productivity Growth in France - Nadal De Simone, Francisco (IMF Working Papers; Working Paper ;, 2003)
Data on the weekly operating time of capital improve the measurement of effective capital input in production. The production function of the French business sector is found to be consistent with a Cobb-Douglas technology under constant returns to scale. Total factor productivity growth, estimated as an unobservable variable, has declined steadily since the late 1970s, but more slowly since 1994. During the 1990s, a secular increase in shift work raised the operating time of capital and began to contribute positively to growth, albeit only slightly.